(untitled) (Journal of Medical & Health Sciences Review, 2025)
Cranioplasty is a surgical procedure used to reconstruct the calvaria, usually following decompressive hemicraniectomy performed for severe head trauma, malignant stroke, hemorrhage, or medically refractory intracranial hypertension. Advances in surgical techniques have enabled preservation of autologous bone flaps, although cranioplasty—regardless of material—remains associated with complications such as infection, seizures, poor cosmesis, hydrocephalus, extra-axial fluid collections, and bone resorption. Failures may arise from implant fabrication issues or surgical technique, and no material is completely risk-free. This study aimed to compare outcomes between subcutaneously preserved autologous bone flaps and polymethyl methacrylate (PMMA) implants. The rationale stemmed from increasing rates of decompressive hemicraniectomies for trauma, infarction, tumors, and venous thrombosis, creating a growing need for reliable cranioplasty materials. A quasi-experimental study design was used, enrolling eligible patients from Neurosurgery Unit II based on surgeon preference. Cranioplasty was performed within four months after resolution of cerebral swelling. Statistical analysis was conducted using SPSS version 27, employing independent t-tests for quantitative variables and chi-square tests for categorical outcomes, with significance set at p ≤ 0.05. The study population had a mean age of 35.72 ± 9.91 years (range 15–62 years). Group A (autologous bone flap) and Group B (PMMA implant) showed similar age and gender distribution. Postoperative outcomes—including infection, cosmesis, hematoma, and revision rates—were monitored over a six-month period. Revision surgery was more common in the autologous bone group: 17.78% vs. 8.89% at one month, 13.33% vs. 4.44% at three months, and 6.67% vs. 0% at six months. Infection rates also favored PMMA, with Group A demonstrating higher infection frequencies at every follow-up (6.67% vs. 2.22% at first month; 6.67% vs. 0% at three months; 4.44% vs. 0% at six months). Cosmetic complications were low in both groups, though slightly higher in Group A during early follow-up.